USING INNOVATIVE METHODS IN TEACHING THE THEME OF DIFFUSION IN VARIOUS MEDIA - R.R. Sultanov,; U.M. Isomaddinova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article presents the use of interactive methods in the teaching of the topic "Diffusion phenomenon in different media" from the 6th grade physics in general secondary schools.